2012
DOI: 10.1088/0022-3727/45/6/062001
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent isolated diamond particles with controllably embedded silicon-vacancy colour centres

Abstract: A technique to fabricate isolated diamond particles with controllably embedded silicon-vacancy (Si-V) colour centres is described. Particle growth and Si doping are performed by microwave plasma-enhanced chemical vapour deposition (CVD) using silane as a source of impurity atoms. The Si-V centres have a strong narrow-band photoluminescence (PL) at room temperature. The dependence of PL intensity of the 738 nm zero-phonon line (ZPL) on silane concentration in the feed-gas mixture exhibits a pronounced maximum. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 28 publications
3
39
0
2
Order By: Relevance
“…A number of impressive results such as demonstration of quantum entanglement of spin states 5 and detection of weak magnetic fields with nano-scale resolution 6 were achieved with the N-V centers. 8,[15][16][17] Several methods were demonstrated to be efficient for synthesis of nano-and micro-diamonds with high concentrations of the Si-V centers. One of the advantages of the 1.68-eV Si-V center is that electronic transitions at this center are very weakly coupled to lattice vibrations resulting in the predominance of the zero-phonon line (ZPL) emission/absorption even in the room temperature spectra.…”
Section: Introductionmentioning
confidence: 99%
“…A number of impressive results such as demonstration of quantum entanglement of spin states 5 and detection of weak magnetic fields with nano-scale resolution 6 were achieved with the N-V centers. 8,[15][16][17] Several methods were demonstrated to be efficient for synthesis of nano-and micro-diamonds with high concentrations of the Si-V centers. One of the advantages of the 1.68-eV Si-V center is that electronic transitions at this center are very weakly coupled to lattice vibrations resulting in the predominance of the zero-phonon line (ZPL) emission/absorption even in the room temperature spectra.…”
Section: Introductionmentioning
confidence: 99%
“…134 Transmission electron microscope (TEM) images of purified NDs confirm that they consist of polyhedra diamond cores of sp 3 carbon atoms, partially coated by a graphitic shell or amorphous carbon. [138][139][140] Nitrogen atoms originate a set of structurally and electronically different local defects 62,141-144 that absorb incident light and emit at characteristic wavelengths. 11.…”
Section: Photophysical Properties Of Fndsmentioning
confidence: 99%
“…In a similar approach, the coupling of the emitting centers to nanofabricated gold antennas was exploited to optically control the NV excited lifetime. 139,140 Si-V color centers in NDs have been recently proposed as markers in the near infrared for cathodoluminescence imaging. 17 the emission spectrum of NV emission matches well the transparency windows of living organism and it is hence well suited for in vivo optical imaging.…”
Section: Photophysical Properties Of Fndsmentioning
confidence: 99%
“…As discussed above in the Introduction, the use of a gaseous mixture of SiH 4 and CH 4 has already been proposed, 24 but it was also demonstrated that concentrations higher than 0.08% (SiH 4 /CH 4 %) affect the diamond crystal structure, therefore an alternative route is necessary to provide massive formation of SiV and good crystalline diamonds. As discussed above in the Introduction, the use of a gaseous mixture of SiH 4 and CH 4 has already been proposed, 24 but it was also demonstrated that concentrations higher than 0.08% (SiH 4 /CH 4 %) affect the diamond crystal structure, therefore an alternative route is necessary to provide massive formation of SiV and good crystalline diamonds.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…24,25 In particular, by using silane, it was demonstrated that the PL intensity strongly depends on the SiH 4 /CH 4 ratio, obtaining the best result at low SiH 4 concentration. The CVD process represents a viable route for the formation of good crystalline quality diamonds, and as previously reported, 12 the inclusion of SiV centers is oen found in CVD diamonds.…”
Section: Introductionmentioning
confidence: 99%